THE CONSTRUCTION , OPERATION AND MAINTENANCE CENTRALIZED ON-BOARD DIAGNOSTICS SYSTEMS AND EMBEDDED CONTROL SYSTEMS AVIONICS OF MODERN AIRCRAFT - Захарченко, В. П.; Ільєнко, C. C.; Курганський, О. Ю.; Мухін, В. В. (Science-based technologies, 2016)
Development of the central board diagnostic systems and embedded systems control the operation of complex automated systems of modern aircraft at the design stage and use them in flight and technical operation during maintenance and repair can reduce the number of random abandoned situations in flight to almost impossible. This, in turn, affected the global strategy of increasing safety (strategy ICAO) has reduced the time and aircraft maintenance in preparation for flight. This complex, multifaceted problem solved by timely informing the pilot during the flight and technical personnel in the service of the SS "on the ground". Maintenance and repair using centralized on-board diagnostic systems and embedded control systems on functional systems of modern aircraft enables to get information on the status and refusal to respond FS and engineering staff in the short term with remote data processing of Refusal situation.